The regime of Demetrius of Phalerum in Athens, 317-307 BCE : a philosopher in politics - O'Sullivan, Lara (Mnemosyne, bibliotheca classica Batava. Supplementum, 2009)
This work draws upon a close re-examination of the literary and epigraphic evidence to offer new understandings of Athenian history during the decade-long rule (317-307 BCE) of the accomplished Peripatetic scholar and renowned legislator, Demetrius of Phalerum.